2022
DOI: 10.3389/fimmu.2022.935374
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Surgery Following Immunochemotherapy in Initially Unresectable Locally Advanced Esophageal Squamous Cell Carcinoma—A Real-World Multicenter Study (RICE-Retro)

Abstract: PurposeThe present study sets out to evaluate the feasibility, safety, and effectiveness of conversion surgery following induction immunochemotherapy for patients with initially unresectable locally advanced esophageal squamous cell carcinoma (ESCC) in a real-world scenario.Materials and MethodsIn this multi-center, real-world study (NCT04822103), patients who had unresectable ESCC disease were enrolled across eight medical centers in China. All patients received programmed death receptor-1 (PD-1) inhibitor pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…This study found that in patients with cT 4b ESCC, the induction regimen of preoperative PD-1 inhibitor combined with albumin-bound paclitaxel + cisplatin resulted in a better pCR rate than did the chemotherapy regimen of albumin-bound paclitaxel + cisplatin alone (23.1% vs. 6.7%). Our findings are consistent with the results reported by Huang ( 17 ) et al., which both confirm that immunochemotherapy results in a better pCR rate (22.4% vs. 6.7%) than does chemotherapy alone in the conversion treatment of cT 4b ESCC. The pCR rate after induction with preoperative chemotherapy in a previous study was 4% ( 9 ), which is similar to 6.7% for chemotherapy alone observed in this study.…”
Section: Discussionsupporting
confidence: 93%
“…This study found that in patients with cT 4b ESCC, the induction regimen of preoperative PD-1 inhibitor combined with albumin-bound paclitaxel + cisplatin resulted in a better pCR rate than did the chemotherapy regimen of albumin-bound paclitaxel + cisplatin alone (23.1% vs. 6.7%). Our findings are consistent with the results reported by Huang ( 17 ) et al., which both confirm that immunochemotherapy results in a better pCR rate (22.4% vs. 6.7%) than does chemotherapy alone in the conversion treatment of cT 4b ESCC. The pCR rate after induction with preoperative chemotherapy in a previous study was 4% ( 9 ), which is similar to 6.7% for chemotherapy alone observed in this study.…”
Section: Discussionsupporting
confidence: 93%
“…After searching for full‐text articles, 51 articles were further excluded because of duplicate publications, a lack of relevant subgroups, incomplete data, or other reasons (e.g., non‐English language). Finally, 27 articles published between 2017 and 2022, 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 were eligible for this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Recent trials have indicated the utility of other ICIs targeting PD-1, and further, use of ICI combination therapy in the perioperative settings may enable high PCR rate, complete resection rate, and thus lead to better survival outcomes. Furthermore, due to the high PCR rate, ICI combination induction therapy may enable curative resection for initially unresectable cases[ 22 , 23 ], and may overcome the treatment results of the current standard chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%